Stabilization of delayed switched positive nonlinear systems under mode dependent average dwell time: A bumpless control scheme. (February 2023) - Nojoumian, Mohammad Ali; Zakerzadeh, Mohammad Reza; Ayati, Moosa
Abstract: This study addresses a Bumpless Transfer (BT) stabilization for a class of switched positive nonlinear systems with time-varying delay. The nonlinear parts of the system are located in a sector of the positive orthant. The contribution of this study is to improve the transient performance of the switched positive systems by proposing a BT performance index at the switching instances and guaranteeing the L 1 –gain performance of the positive systems. A novel piecewise-continuous multiple Lyapunov–Krasovskii functional is utilized in the system's stability analysis and control design. The control design methodology is established under Mode Dependent Average Dwell Time. Also, the BT stabilization of the system under asynchronous switching conditions is developed. Finally, a numerical example is provided to depict the effectiveness of the results. Highlights: Improving transient response of delayed switched positive systems by providing Bumpless Transfer performance. Deriving stability condition by utilizing MDADT strategy. Reducing stability conditions conservativity by proposing multiple piecewise-continuous linear copositive L–K functional. Extension of the Bumpless Transfer performance for delayed switched positive systems with asynchronous switching conditions. Calculating L 1 gain performance of the closed-loop system in synchronous and asynchronous switching modes.